NON-QUALITATIVE APPROACH TO ENGLISH TEACHER IDENTITY RESEARCH: A SYSTEMATIC REVIEW (2012-2022) - Yiqian Yan; Madhubala Bava Harji (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The qualitative approach appears to be dominant in language teacher identity (LTI) research. Emerging LTI studies using non-qualitative methods have been overlooked. To date, a review that synthesizes English teacher identity (ETI) studies using non-qualitative methods is lacking. This paper reports on a PRISMA-based systematic review of 20 identified studies from the Google Scholar and CNKI databases. The outcomes of the review are as follows: First, studies tend to concentrate on five countries, but mostly in China and Iran. Second, Beijaard’s definition and measuring instruments of TI are most frequently cited. Third, samples were predominantly university teachers. Finally, a framework was proposed to capture six research themes: (i) ETI levels and socio-demographic factors, (ii) comparative study, (iii) ETI and one construct, (iv) ETI and two constructs, and (v) ETI and technology use or metacognition. Recommendations for future research and limitations of this study are discussed.